Is Truth to Post-Truth what Modernism Is to Postmodernism? Heidegger, the Humanities, and the Demise of Common-Sense - Klaus Benesch (European Journal of American Studies)
This essay argues that there is no such thing as post-truth. We are by no means in the middle of an unprecedented epistemological crisis that keeps us from telling right from wrong. Rather, what we currently witness is a major breakdown of the institutions and mechanics of democratic society, triggered by an encompassing technological transformation that affects both our public and private lives. Even if the challenges for rational public discourse are real, they should not be countered by philosophy but by concerted, serious interventions in the political arena. This essay’s approach to the issue of post-truth, therefore, is threefold: First, it looks at how most of us in the West have come to agree on certain truths about truth. Second, since the notion of post-truth is often invoked to expose someone who fails to speak the truth (rather than to demote the concept of truth altogether), it refers to the Greek tradition of parrhesia as discussed by the late Michel Foucault. And thirdly, this essay comments on the alarming rise of anti-professionalism. Long before neoconservatives waged war on the university, the erosion of expertise has been fostered, according to Bruno Latour, by forces unleashed within the humanities itself. Yet there is little evidence, this essays concludes, that humanist critical thinking is driving the current post-truth crisis and that postmodernist efforts to rethink and question modernist forms of critique should be undone altogether.